2019
DOI: 10.4018/978-1-5225-7829-1.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Assessing Critical Thinking and Clinical Reasoning Skills in Medical Education

Abstract: In recent years, there has been more emphasis on developing higher order thinking (e.g., critical thinking and clinical reasoning) processes to tackle the recent trends and challenges in medical education. Critical thinking and clinical reasoning are considered to be the cornerstones for teaching and training tomorrow's doctors. Lack of training of critical thinking and clinical reasoning in medical curricula causes medical students and physicians to use cognitive biases in problem solving which ultimately le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…More than twothirds of the reported mistakes in diagnosis are linked to physician's lack of critical thinking ability in the present context. Given the belief that healthcare professionals must be logical thinkers, there is no consensus on the most successful model to teach and evaluate critical thinking and clinical reasoning skills (8). Recent research, which evaluated a wide range of quantitative and qualitative competencies, including behavioural and communication skills, showed that the OSCE was valid and reliable and essential for positive educational effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than twothirds of the reported mistakes in diagnosis are linked to physician's lack of critical thinking ability in the present context. Given the belief that healthcare professionals must be logical thinkers, there is no consensus on the most successful model to teach and evaluate critical thinking and clinical reasoning skills (8). Recent research, which evaluated a wide range of quantitative and qualitative competencies, including behavioural and communication skills, showed that the OSCE was valid and reliable and essential for positive educational effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are limited in their lack of measuring the particular aspect of health profession-related attributes, inability to evaluate medical professionals' practical reality, and effectively assess psychometric properties (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is a tool to form conclusions, judgments, or inferences from facts or premises [6]. Clinical reasoning is a context dependent way of thinking and decision making in professional practice to guide practice actions [7]. We discussed fallacy-free reasoning in medicine in more detail elsewhere [8].…”
Section: Some Philosophical Contributions To Cherish and Develop In The Futurementioning
confidence: 99%
“…Critical thinking in medicine deserves more detail and discussion, as also presented elsewhere [49][50][51][52].…”
Section: What Are Ebm's Applications and Uses Across The Health Sciences?mentioning
confidence: 99%